Physiological and Transcriptomic Responses to Nitrogen Deficiency in Neolamarckia cadamba - Lu, Lu; Zhang, Yuanyuan; Li, Lu; Yi, Na; Liu, Yi; Qaseem, Mirza Faisal; Li, Huiling; Wu, Ai-Min (Frontiers in Plant Science, 2021)
Nitrogen is one of the abundant and essential elements for plant growth and development, and its deficiency affects plants at both physiological and genetic levels. It is known that nitrogen deficiency (ND) stifles growth in Neolamarckia cadamba, a woody, fast-growing plant. However, the physiological and molecular mechanisms of ND have not been well investigated till now. Here we studied N. cadamba responses to ND under hydroponic conditions. ND led to reduction in biomass, chlorophyll content and photosynthetic capacity. The activities of glutamine synthetase and nitrate reductase were decreased in root and increased in leaf. The lignin content of stem increased as the duration of stress increased. Many genes including transcription factors such as NIN-LIKE PROTEIN 7 (NLP7), TGACG motif-binding factor 1 (TGA1), BHLH45, NAC43, and basic region/leucine zipper pattern 44 (bZIP44) expression were found to be up-regulated in transcriptome analysis. The expression of transporters such as nitrate regulation transporter 2.4 (NRT2.4), ammonium transporter 3 (AMT3), and amino acid transporter protein 3 (AAP3) was up-regulated. In addition, the expression of phosphorus and calcium related genes such as phosphate starvation response 2 (PHR2) and Cyclic nucleotide-gated ion channel 15 (CNGC15) were up-regulated in response to ND stress. Our results reveal the physiological and molecular mechanisms by which woody plants respond to ND.